Knots "Choke Off" Polymers upon Stretching. Issue 2 (2nd December 2015) - Stauch, Tim; Dreuw, Andreas
Abstract: Long polymer chains inevitably get tangled into knots. Like macroscopic ropes, polymer chains are substantially weakened by knots and the rupture point is always located at the "entry" or "exit" of the knot. However, these phenomena are only poorly understood at a molecular level. Here we show that when a knotted polyethylene chain is tightened, most of the stress energy is stored in torsions around the curved part of the chain. The torsions act as "work funnels" that effectively localize mechanical stress in the immediate vicinity of the knot. As a result, the knot "chokes" the chain at its entry or exit, thus leading to bond rupture at much lower forces than those needed to break a linear, unknotted chain. Our work not only explains the weakening of the polymer chain and the position of the rupture point, but more generally demonstrates that chemical bonds do not have to be extensively stretched to be broken. Abstract : The force chokes : A polymer chain is substantially weakened by a knot and ruptures at its "entry" or "exit", because the torsions in the curved part of the chain act as "work funnels" that localize the mechanical stress in this region. As a result, the knot chokes off the chain in its immediate vicinity. This shows that bonds do not have to be extensively stretched to be broken in mechanochemical pulling experiments.